Perilaku Terorisme - Milla, Mirra Noor (Faculty of Psychology, Universitas Surabaya, 2006)
Psychological studies on terrorism were mostly conducted through motivational explanations of terrorism. Initiated with a cognitive dissonance condition on the individual level, an individual would be brought to join the same dissonance group toward a relative deprivation on a macro level. Through a personal track model, each individual came into a terrorist group through a series of stages to reach the individual's readiness to execute a terrorism act. Ultimately, the individual experiences a loosened moral when he/she conducts the terrorism act, consisting of moral justification, blaming, and dehumanuzing the victims. Kajian psikologi ini tentang terorisme banyak dilakukan melalui penjelasan motivasi terorisme. Diawali dengan kondisi disonansi kognitif pada level (aras) individu, seseorang akan dibawa untuk bergabung pada kelompok disonansi yang sama menuju deprivai relatif pada aras makro. Melalui model jalur personal masing-masing, individu masuk dalam kelompok teroris dengan proses serangkaian tahapan untuk kemudian sampai pada kesiapan seseorang melakukan aksi terorisme. Pada akhirnya, seseorang akan mengalami perenggangan moral ketika ia melakukan aksi terorisme, yang meliputi justifikasi moral, menyalahkan dan dehumanisasi korban.